Substantial Intestinal Microbiota Differences Between Patients With Ulcerative Colitis From Ghana and Denmark - Mirsepasi-Lauridsen, Hengameh Chloé; Vranckx, Katleen; Nielsen, Henrik Vedel; Andersen, Lee O’Brien; Archampong, Timothy; Krogfelt, Karen Angeliki; Petersen, Andreas Munk (Frontiers in Cellular and Infection Microbiology, 2022)
Background Ulcerative colitis (UC) is a relapsing nontransmural inflammatory disease that is restricted to the colon and is characterized by flare-ups of bloody diarrhea. In this study, we aimed to investigate intestinal bacterial diversity in healthy controls and patients with UC with and without active disease, from Ghana and Denmark. Methods The study included 18 UC patients (9 with active and 9 with inactive disease) and 18 healthy controls from Ghana. In addition 16 UC patients from Denmark (8 UC with active and 8 UC with inactive disease) and 19 healthy controls from Denmark. Microbiota diversity analysis relied on sequencing of ribosomal small subunit genes. Purified genomic DNA was submitted to PCR using a primer set targeting prokaryotes and eukaryotes. The purified DNA was sequenced on the Illumina MiSeq system in a 2 × 250 bp set up (Illumina, San Diego, CA, USA). Blinded analysis of the taxonomy table was performed using BioNumerics-7.5 (Applied Maths NV, Sint-Martens-Latem, Belgium). Results When analyzing the taxonomy data for prokaryotes, cluster and principal component analysis shows Danish healthy controls clustered together, but separate from healthy controls from Ghana, which also clustered together. The Shannon diversity index (SDI) for prokaryotes shows significant differences between Danish healthy controls and patients in comparison with the corresponding groups from Ghana (p = 0.0056). Significant increased abundance of Escherichia coli was detected in healthy controls from Ghana in comparison with healthy controls from Denmark. The SDI of the prokaryotes ranges between 0 and 3.1 in the Ghana study groups, while in the Danish study groups it ranges between 1.4 and 3.2, the difference is however not significant (p = 0.138). Our data show a significant increased abundance of eukaryotes species in the healthy control group from Ghana and Denmark in comparison with patient groups from Ghana and Denmark. Conclusion Overall, healthy controls and patients with UC from Denmark have increased diversity of prokaryotes. Healthy controls from Denmark and Ghana have increased abundance of eukaryotes in comparison with UC patient groups from Denmark and Ghana.